Scrutinizing the Strategies of EFL Teachers in Instructing Listening Skills in the Classroom - Hilly, Sakinah F.; Hasan, Jhems (Journal of English Teaching and Linguistic Issues (JETLI), 2024)
The listening process in the classroom involves a series of steps that students go through as they receive, interpret, and respond to spoken language. This study aims at scrutinizing the strategies of EFL teachers in instructing listening skill in the classroom. The research data was first described in a quantitative descriptive manner using the frequency format on the results of the questionnaire which was distributed to 46 students at SMP N 3 Limboto, Gorontalo. In addition, further research data is the result of interviews with two English teachers at the school regarding listening learning strategies so far. The findings of this study revealed that the EFL teachers in SMP 3 Limboto used a variety of listening learning strategies that are quite similar to one another. They have a solid understanding of the goals that should be accomplished by students at the junior high school level while using listening resources. They draw from a variety of sources, including books and the extensive online content available now, when putting together listening materials. The model for learning through hearing should be engaging and have a variety of components, and the utilisation of various learning media should be enabled by modern technology. The method of evaluation should incorporate activities at various points throughout the learning process and make use of a rubric as an assessment tool to determine the level of listening ability possessed by the students. The results of the student questionnaire regarding the teacher's strategy also confirmed the correctness of the strategy conveyed by the two teachers during the interview. These results certainly illustrate that the English teacher at SMP N 3 is quite good at teaching listening to students by paying attention to variations in strategies when learning takes place in the classroom.